Nerve regeneration induction tube
By adopting a cylindrical mold with a multi-layer structure, the connection layer provides flexibility and avoids soap angle formation while ensuring the hardness of the cylindrical body, the problem of insufficient soap angle formation and pressure resistance during bending or deforming of existing medical equipment is solved, and the balance between flexible deformation and pressure resistance is achieved.
Patent Information
- Application Number
- JP2021518685
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-19
- Filing Date
- 2021-03-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-03-12
AI Technical Summary
When cylindrical molds in existing medical equipment are bent or deformed, they are prone to soap angles, resulting in lumen obstruction and tissue damage, and at the same time there are shortcomings in pressure resistance.
A multi-layer structural cylindrical mold consisting of a plurality of cylindrical bodies and connecting layers is employed, the connecting layer is located outside or inside of the cylindrical body, providing flexibility to avoid soap angle formation, while the hardness of the cylindrical body ensures pressure resistance.
When external forces cause bending or deformation, this design can flexibly deform to avoid soap angle formation while maintaining sufficient pressure resistance and protecting internal tissue.
Smart Images

Figure 0007661881000006 
Figure 0007661881000007 
Figure 0007661881000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a cylindrical molded body for a medical device. [Background technology]
[0002] When a tissue defect or disorder occurs in the human body, implant treatment is performed by implanting a molded body made of a material harmless to the human body for the purpose of replacing or supporting the original tissue. Cylindrical molded bodies with a hollow interior are often used in implant treatment, and are used for various medical purposes, such as surrounding and protecting tissue, filling the hollow part with a drug for sustained release, and replacing tubular tissue such as blood vessels and nerves. A nerve regeneration induction tube is known as a cylindrical molded body that induces nerve regeneration for treatment. By using a nerve regeneration induction tube, the intrusion of connective tissue, which is an obstacle to nerve regeneration, into the damaged area is suppressed.
[0003] FIG. 1 is a diagram for explaining an example of the use of a conventional nerve regeneration induction tube. In the nerve regeneration induction tube 10 shown in FIG. 1, nerve cells 200 and Schwann cells 210 are arranged on one end side. The inside of the nerve regeneration induction tube 10 is filled with a scaffold material 11. In the nerve regeneration induction tube 10, Schwann cells 211 grow inside. Axons 201 extend inside the grown Schwann cells 211. During this time, the nerve regeneration induction tube 10 inhibits the intrusion of connective tissue, thereby inhibiting the path along which the axons 201 attempt to extend from being blocked. In this way, nerve regeneration using the nerve regeneration induction tube 10 proceeds.
[0004] Meanwhile, research has been conducted into shapes that improve the strength of nerve regeneration-inducing tubes in order to protect the nerves that regenerate within the tube. For example, Patent Document 1 reports a tubular body made of a single-layer structure of braided cord, in which threads formed from multiple organic polymer fibers are braided at a braiding angle of 50° to 87.5°. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-155622 A Summary of the Invention [Problem to be solved by the invention]
[0006] If the strength of the tube is high, it can provide strong resistance to pressure that crushes the short axis of the tube, and can protect the inside. However, if the strength of the tube is too high, it will not be flexible enough to withstand deformation due to bending or bending, and there is a risk of damaging the tissues around the transplant site. On the other hand, if flexibility is added by simply adjusting the Young's modulus of the tube, kinking occurs when the tube is bent, which can cause blockage of the tube or damage to the internal tissue.
[0007] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a tubular molded body for medical devices that, when an external force is applied due to bending or bending, can flexibly deform in response to bending or bending while maintaining the pressure resistance of the tube, thereby suppressing the occurrence of kinking. [Means for solving the problem]
[0008] In order to solve the above problems, the present invention is as follows.
[0009] A cylindrical molded body for a medical device, comprising a plurality of cylindrical bodies and a connecting layer connecting the cylindrical bodies.
[0010] A medical device comprising the above molded article.
[0011] A nerve regeneration induction tube comprising the above-mentioned molded body. Effect of the Invention
[0012] According to the cylindrical molded body for medical devices of the present invention, the flexible layer connecting the multiple cylindrical bodies allows the cylindrical molded body to flexibly deform when bent or flexed, and the occurrence of kinking can be suppressed. The cylindrical molded body for medical devices of the present invention can be suitably applied to nerve regeneration induction tubes. The nerve regeneration induction tube of the present invention is particularly useful for regeneration of muscle tissue, vascular tissue, nerve tissue, spinal cord tissue, skin tissue, etc. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram illustrating an example of the use of a conventional nerve regeneration-inducing tube. [Diagram 2] FIG. 13 is a schematic diagram of an embodiment in which the cylindrical body and the connecting layer are in contact with each other and the connecting layer is disposed on the outside of the cylindrical body. [Diagram 3] FIG. 13 is a schematic diagram of an embodiment in which a cylindrical body and a connecting layer are in contact with each other and the connecting layer is disposed inside the cylindrical body. [Figure 4] FIG. 13 is a schematic diagram of an embodiment in which the cylindrical body and the connecting layer are in contact with each other and the connecting layer is disposed on the outside of the cylindrical body. [Diagram 5] FIG. 13 is a schematic diagram of an embodiment in which a cylindrical body and a connecting layer are in contact with each other and the connecting layer is disposed inside the cylindrical body. [Figure 6] FIG. 1 is a schematic diagram showing an embodiment in which the cylindrical bodies and the connecting layer are in contact with each other, and the connecting layer is disposed on the inside of the cylindrical body A and on the outside of the cylindrical body B. [Figure 7] Photographs of the cylindrical molded bodies for medical instruments of the Examples and Comparative Examples in a state where they were bent at an angle of 60° in Measurement Example 6. [Figure 8] Photograph showing the kink resistance of the cylindrical molded article for a medical instrument of Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. Note that the present invention is not limited to the following embodiments. Furthermore, each drawing referred to in the following description merely shows the shape, size, and positional relationship in a schematic manner to the extent that the contents of the present invention can be understood. In other words, the present invention is not limited to only the shape, size, and positional relationship exemplified in each drawing. Furthermore, in the description of the drawings, the same parts are given the same reference numerals.
[0015] The cylindrical molded body for medical devices of the present invention has a plurality of cylindrical bodies and a connecting layer connecting the cylindrical bodies. That is, the molded body of the present invention has at least two cylindrical bodies. The part where two adjacent cylindrical bodies are connected by the connecting layer is called a connecting part. The cylindrical molded body for medical devices of the present invention has at least one connecting part. The number of cylindrical bodies is not limited to two, and the number of connecting parts is not limited to one. That is, the molded body of the present invention is not particularly limited in the number of cylindrical bodies and the number of connecting parts, and may have, for example, three cylindrical bodies and two connecting parts.
[0016] The cylindrical molded article for medical devices of the present invention exhibits pressure resistance by having a hard cylindrical body, and exhibits flexibility and kink resistance against bending and bending by having a soft connecting layer. If the interval between adjacent cylindrical bodies is too large, the pressure resistance cannot be sufficiently exhibited, so the interval between adjacent cylindrical bodies is preferably 1 mm or less. The lower limit of the interval between adjacent cylindrical bodies is not particularly limited, but it is preferable that there is no interval, that is, the interval is 0 mm.
[0017] The interval between adjacent cylindrical bodies is the distance from the end of one cylindrical body to the end of the other cylindrical body close to the end when no external force is applied to the molded body and the connecting layer does not expand or contract relative to the initial state, and can be measured with a vernier caliper or the like. In addition, in the case of a molded body having a structure in which one cylindrical body is inserted inside the other cylindrical body, that is, as described below, in the case of a state in which the inner diameter A of one cylindrical body A is larger than the outer diameter B of the other cylindrical body B at the connecting part and the cylindrical body B is inserted inside the cylindrical body A, there is no interval between adjacent cylindrical bodies, so the interval between adjacent cylindrical bodies is 0 mm. Here, the initial state refers to a state in which no external force has been applied to the molded body in the longitudinal direction after its creation.
[0018] Also, if the length of the cylindrical body is too short, it will not be able to exhibit pressure resistance, so the length of the cylindrical body in the direction along the longitudinal axis of the molded body is preferably 1.0 mm or more, whereas if the length of the cylindrical body is too long, it will not be able to exhibit sufficient flexibility, so the length of the cylindrical body in the direction along the longitudinal axis of the molded body is preferably 10 mm or less.
[0019] In the cylindrical molded article for medical device of the present invention, a plurality of cylindrical bodies are connected by a connecting layer. As shown in Fig. 2, the connecting layer is preferably disposed on the outside of the cylindrical bodies, and as shown in Fig. 3, the connecting layer is preferably disposed on the inside of the cylindrical bodies.
[0020] As shown in Figs. 4 to 6, the cylindrical molded body for medical device of the present invention may be configured such that the inner diameter of one cylindrical body A is larger than the outer diameter of one cylindrical body B in the connecting portion, and the connecting portion is configured so that the cylindrical body B can be inserted inside the cylindrical body A. Here, the inner diameter of the cylindrical body is the diameter of the inner circle of the vertical cross section of the short axis of the cylindrical body. Also, the outer diameter of the cylindrical body is the diameter of the outer circle of the vertical cross section of the short axis of the cylindrical body. In this case, as shown in Fig. 4, the cylindrical body and the connecting layer are in contact with each other, and the connecting layer is disposed on the outside of the cylindrical body; as shown in Fig. 5, the cylindrical body and the connecting layer are in contact with each other, and the connecting layer is disposed on the inside of the cylindrical body; as shown in Fig. 6, the cylindrical body and the connecting layer are in contact with each other, and the connecting layer is disposed on the inside of one cylindrical body (cylindrical body A) and on the outside of the other cylindrical body (cylindrical body B) of the adjacent cylindrical bodies.
[0021] In this embodiment, when the molded body is pressed in from both ends, cylindrical body B can be inserted inside cylindrical body A. At the connecting portion, cylindrical body B may or may not be inserted inside cylindrical body A.
[0022] Furthermore, in the cylindrical molded article for medical devices of the present invention, a plurality of cylindrical bodies are connected by a connecting layer, so that the entire molded article has a cylindrical shape.
[0023] When the cylindrical molded body for medical devices of the present invention is used as a medical device such as a nerve regeneration induction tube, it is assumed that the molded body is placed inside or outside the living body, and therefore an external force is applied to the molded body due to deformation such as compression, bending, and bending. Therefore, in order to protect the inside of the cylindrical body forming the cylindrical molded body from compression, it is preferable that the Young's modulus of the cylindrical body is 6.3 MPa or more. Assuming that there is a hard tissue such as bone around the placement site, it is more preferable that the Young's modulus of the cylindrical body is 10 MPa or more. On the other hand, when used for regeneration induction of tissues (e.g., fascia, tendons, ligaments, nerves, muscles, etc.) that are softer than hard tissues such as bones and teeth, pain may occur if the tube is too hard, so the Young's modulus of the cylindrical body is preferably 100 GPa or less, more preferably 10 GPa or less, and even more preferably 1 GPa or less.
[0024] In addition, the Young's modulus of the connecting layer connecting the cylindrical bodies is preferably less than 6.3 MPa. In this way, the cylindrical body can exhibit flexibility and deform in response to deformation such as bending and bending, and the occurrence of kinking of the cylindrical body can be suppressed. This is preferable because it can protect the tissue inside the cylindrical body from compression. On the other hand, if the Young's modulus of the connecting layer is too low, the connecting strength becomes insufficient, and the cylindrical body may be disengaged when the cylindrical body is bent or curved, or the connecting portion may be crushed or kinked. Therefore, although the Young's modulus of the connecting layer is not limited, it is preferable that it is 1 MPa or more.
[0025] The cylindrical molded article for medical devices of the present invention can be suitably used for medical devices, particularly nerve regeneration-inducing tubes. Therefore, the following will explain the details by taking as an example a nerve regeneration-inducing tube using the molded article of the present invention.
[0026] (Embodiment) A nerve regeneration-inducing tube according to an embodiment of the present invention is composed of a plurality of cylindrical bodies and a connecting layer that connects the plurality of cylindrical bodies.
[0027] To prevent fibrous tissue or cells from entering through gaps in the connecting parts, the connecting layer preferably covers all the connecting parts, and more preferably covers the entire cylindrical molded body for medical devices.
[0028] By having a structure in which multiple cylindrical bodies are connected by a connecting layer, the cylindrical bodies on both sides of the connecting part become movable, enabling flexibility and suppression of kink occurrence. The number of connecting parts contained in the cylindrical molded body for medical devices is preferably one or more, and more preferably four or more in order to sufficiently suppress the occurrence of kinking. From the viewpoint of reducing the durability of the tube, the number of connecting parts is preferably 100 or less.
[0029] In a cylindrical molded body for medical devices, the inner diameter A of one of the adjacent cylindrical bodies A is larger than the outer diameter B of the other cylindrical body B, and the connecting portion is configured so that the cylindrical body B can be inserted inside the cylindrical body A. This is preferable because when pressure occurs to compress the molded body in the longitudinal direction, the cylindrical body B is inserted into the cylindrical body A to buffer the pressure. The length of the part of the cylindrical body B inserted into the cylindrical body A is X. The length of the cylindrical body A that is not inserted into the cylindrical body B is Y. The length of the cylindrical body B that is not inserted into the cylindrical body A is Z. In order to prevent the center of the cylindrical body B and the cylindrical body A from being misaligned in the cylindrical body, X is preferably greater than 0. In addition, since the portion where cylindrical body B moves within cylindrical body A becomes a buffer region, the sum of the smaller values of Y and Z at each connecting portion is preferably 5% or more of the length of the cylindrical molded body for medical device, and preferably 50% or less.
[0030] The length of the multiple cylindrical bodies constituting the cylindrical molded body for medical devices may be uniform, or cylindrical bodies of different lengths may be used. From the viewpoint of exhibiting flexibility when the cylindrical molded body for medical devices is bent and suppressing the occurrence of kinking, the length of the cylindrical body is preferably 10 mm or less. From the viewpoint of increasing the connection strength of the connection layer, the length of the cylindrical body is preferably 1.0 mm or more.
[0031] The inner diameter of the cylindrical molded body for medical devices of the present invention is preferably selected according to the site of use, and for example, in the case of a nerve regeneration induction tube, 20 mm to 0.5 mm is preferable. The inner diameters of both ends of the cylindrical molded body for medical devices are not limited to be the same. By having a difference in inner diameter at both ends, it is easy to connect nerves of different thicknesses on the central side and the peripheral side, and it is possible to prevent the thin peripheral side nerve from falling off. The difference between the inner diameter of one end and the inner diameter of the molded body of the present invention, that is, the difference between the inner diameters of both ends, is preferably 0 mm or more and 20 mm or less.
[0032] The higher the strength of the cylindrical molded body for medical devices, the more the protrusion accidents can be suppressed, so the Young's modulus of the cylindrical body is preferably 6.3 MPa or more. On the other hand, since the flexibility of the cylindrical molded body for medical devices is exhibited by the connection layer, the Young's modulus of the connection layer is preferably less than 6.3 MPa. The Young's modulus of the cylindrical body can be measured by cutting out the relevant part from the cylindrical molded body and performing a tensile test described later. The Young's modulus of the connection layer can be measured by performing a tensile test on the cylindrical molded body as described in Measurement Example 8 described later. Alternatively, the Young's modulus of the connection layer can be measured by dissolving the polymer used for the connection layer in a solvent to produce a film as described in Measurement Example 3 described later, and performing a tensile test on the film.
[0033] When an external force is applied to the cylindrical molded body for medical devices of the present invention by bending or bending, the soft connecting layer expands and contracts, which allows flexibility and suppresses the occurrence of kinks, so it is desirable for the cylindrical molded body for medical devices to spontaneously restore to its original length after deformation. For this reason, it is preferable to use a material with restoring properties for the connecting layer. The restoring properties can be quantitatively evaluated by determining the work load preservation rate as in Measurement Example 5 described later. The work load preservation rate is the ratio of the work load at the 10th operation to the work load at the first operation when an operation in which a tensile stress is applied in the longitudinal direction of the cylindrical molded body to generate a tensile strain of 100% with respect to the initial length is repeated 10 times, and can be calculated by the method described in Measurement Example 5 described later. The closer the work load preservation rate of the material used for the connecting layer is to 100%, the easier it is for the molded body to restore its length after pressure buffering. Since the molded body used in the vicinity of the muscle is frequently deformed, the work load preservation rate of the cylindrical molded body for medical devices of the present invention is preferably 55% or more, and the work load preservation rate of the cylindrical molded body used in a site where frequent large deformation occurs due to bending or bending, such as a joint, is more preferably 60% or more.
[0034] The tensile strength is a factor directly related to the breaking strength of the cylindrical molded body. Assuming that the cylindrical molded body is used in a portion subjected to external force due to deformation such as muscle expansion or contraction, the tensile strength of the cylindrical molded body is preferably 5 MPa or more. For a cylindrical molded body used in a portion subjected to more severe deformation such as bending or curvature, the tensile strength of the cylindrical molded body is preferably 20 MPa or more.
[0035] The breaking elongation is a factor indicating the breaking strength of the cylindrical molded body. Assuming that the cylindrical molded body is used in a part that is subjected to external forces such as muscle expansion and contraction, vibration, etc., the breaking elongation of the cylindrical molded body is preferably 200% or more. For a cylindrical molded body used in a part where more severe deformation such as bending or curvature occurs, the breaking elongation is preferably 500% or more. For a cylindrical molded body used in a part where particularly large deformation occurs due to bending or curvature, such as a joint, the breaking elongation is more preferably 1000% or more. The breaking elongation is a value measured according to JIS K6251 (2010) (written as "elongation at break" in JIS), and specifically, it is measured by a tensile test described later.
[0036] In addition, since the cylindrical molded body for medical devices of the present invention is used by being placed inside or outside the living body, it is expected that it will be repeatedly subjected to forces due to the movement of muscles and joints, and will repeatedly deform and restore. Therefore, the molded body is required to be durable against repeated deformation. Durability can be quantitatively evaluated by measuring the permanent strain generated when measuring the work retention rate. Since the cylindrical molded body used in the vicinity of muscles is frequently deformed, the permanent strain of the cylindrical molded body is 20% or less, and the permanent strain of the cylindrical molded body used in a site where frequent large deformation occurs due to bending or curvature, such as a joint, is preferably 15% or less.
[0037] The cylindrical molded body for medical devices of the present invention is preferably made of a bioabsorbable polyester, since it can exhibit bioabsorbability by containing the bioabsorbable polyester. The blending ratio is not limited as long as the bioabsorbability required for each application is exhibited, but it is generally preferable that the cylindrical molded body contains the bioabsorbable polyester in an amount of 50% by weight or more, and more preferably 80% by weight or more. When it is required that the bioabsorbable polyester completely disappears when applied to a living body, it is preferable that the cylindrical molded body is made of only the bioabsorbable polyester.
[0038] Since the tubular molded article for medical device of the present invention contains a bioabsorbable polyester, it is preferable that the tubular body constituting the tubular molded article contains a bioabsorbable polyester.
[0039] Here, bioabsorbability refers to the property of being naturally decomposed by hydrolysis or enzymatic reaction after placement inside or outside the living body, and disappearing by metabolism or excretion of the decomposition products. Examples of such bioabsorbable polyesters include polyesters selected from the group consisting of polyglycolic acid, polylactic acid (D, L, DL form), polyε-caprolactone, polyhydroxybutyric acid, polyhydroxybutyrate valeric acid, polyorthoester, polyhydroxyvaleric acid, polyhydroxyhexanoic acid, polybutylene succinate, polybutylene succinate, polyethylene trimethylene terephthalate, polyhydroxyalkanoate, and copolymers thereof. Among them, it is more preferable that the cylindrical body contains any one of polyglycolic acid, a copolymer of polylactic acid and polyglycolic acid, and a copolymer of polyglycolic acid and polyε-caprolactone.
[0040] In a preferred embodiment, the tie layer contains, as the bioabsorbable polyester, a polyester copolymer having as its main constituent units monomer residues selected from hydroxycarboxylic acid residues and lactone residues, and in a more preferred embodiment, a polyester copolymer having as its main constituent units two types of monomer residues, hydroxycarboxylic acid residues and lactone residues. Lactones are cyclic compounds formed by intramolecular dehydration condensation of the hydroxyl group and the carboxyl group of a hydroxycarboxylic acid.
[0041] Here, the term "main structural unit" means that the monomer residue accounts for 50 mol % or more of the total number of residues in the entire polymer, including other monomer residues. Also, the term "main structural units" means that the sum of the number of the two monomer residues accounts for 50 mol % or more of the total number of residues in the entire polymer, including other monomer residues, and each of the two types of residues accounts for 20 mol % or more of the total number of residues in the entire polymer.
[0042] For example, the term "main structural units are hydroxycarboxylic acid residues and lactone residues" means that the sum of the number of hydroxycarboxylic acid residues and lactone residues is 50 mol% or more of the number of residues in the entire polymer, the number of hydroxycarboxylic acid residues is 20 mol% or more of the number of residues in the entire polymer, and the number of lactone residues is 20 mol% or more of the number of residues in the entire polymer. The molar fraction of each monomer residue can be determined by the area value of the signal derived from each residue by nuclear magnetic resonance (NMR) measurement. For example, when the hydroxycarboxylic acid residue is a lactic acid residue and the lactone residue is a caprolactone residue, it can be measured by the method described in Measurement Example 2 below.
[0043] As a monomer for forming a hydroxycarboxylic acid residue, an aliphatic hydroxycarboxylic acid is particularly preferred. Examples of the aliphatic hydroxycarboxylic acid include lactic acid, glycolic acid, hydroxybutyric acid, hydroxyvaleric acid, hydroxypentanoic acid, hydroxycaproic acid, and hydroxyheptanoic acid, and in particular, lactic acid, glycolic acid, and hydroxycaproic acid are preferred. As the lactic acid, L-lactic acid, D-lactic acid, and mixtures thereof can be used. In terms of the physical properties and biocompatibility of the resulting polymer, it is preferable to use lactic acid, and in particular, it is more preferable to use L-lactic acid. When a mixture is used as a monomer, the content of the L-isomer is preferably 85 mol% or more, and more preferably 95 mol% or more.
[0044] As a monomer for forming a hydroxycarboxylic acid residue, lactide, which is a cyclic compound formed by dehydration condensation of the hydroxyl group and the carboxyl group of two molecules of hydroxycarboxylic acid, may be used. As lactide, dilactide formed by dehydration condensation of two molecules of lactic acid, glycolide formed by dehydration condensation of two molecules of glycolic acid, and tetramethylglycolide may be used.
[0045] Examples of monomers for forming lactone residues include ε-caprolactone, dioxepanone, ethylene oxalate, dioxanone, 1,4-dioxane-2,3-dione, β-propiolactone, δ-valerolactone, β-propiolactone, β-butyrolactone, γ-butyrolactone, and pivalolactone.
[0046] In addition, derivatives of the above-exemplified monomers can also be used.
[0047] In this specification, the term "monomer residue" contained in a polyester copolymer generally refers to a repeating unit of a chemical structure derived from the monomer in the chemical structure of a polyester copolymer obtained from a polymerization stock solution containing the monomer. For example, the repeating unit of a chemical structure derived from lactic acid (CHCH(OH)COOH) and ε-caprolactone (formula below)
[0048] [ka]
[0049] When the copolymer of lactic acid and caprolactone is polymerized, the unit represented by the following formula is obtained.
[0050] [ka]
[0051] is a lactic acid monomer residue, and the unit represented by the following formula is an ε-caprolactone monomer residue.
[0052] [ka]
[0053] However, as an exception, when a dimer such as lactide is used as a monomer, the term "monomer residue" refers to one of the two repeating structures derived from the dimer. For example, dilactide (L-(-)-lactide: formula below)
[0054] [ka]
[0055] When ε-caprolactone is polymerized, the chemical structure of the copolymer has a structure in which the structure shown in the above formula (R1) is repeated twice as a dilactide residue. In this case, one lactic acid unit is regarded as a "monomer residue", and two "monomer residues", i.e., lactic acid residues, are considered to be formed derived from dilactide.
[0056] The weight-average molecular weight of the bioabsorbable polyester used in the present invention is preferably 100,000 or more in order to obtain the effect of improving tensile strength by entanglement of polymer chains. The upper limit is not particularly limited, but considering the problems in the manufacturing process due to the increase in viscosity and the decrease in moldability, it is preferably 1.6 million or less, more preferably 800,000 or less, and even more preferably 400,000 or less. The weight-average molecular weight can be determined by gel permeation chromatography (GPC), specifically, by the method described in Measurement Example 1 below.
[0057] Hereinafter, a polyester copolymer having hydroxycarboxylic acid residues and lactone residues as main constituent units, which is a particularly preferred bioabsorbable polyester in the present invention, will be described.
[0058] In the polyester copolymer, the sum of the hydroxycarboxylic acid residues and the lactone residues is, as defined above, 50 mol% or more of the entire polymer including other monomer residues, preferably 75 mol% or more, and more preferably 90 mol% or more. Also, as defined above, each of the hydroxycarboxylic acid residues and the lactone residues is 20 mol% or more, preferably 30 mol% or more, and more preferably 40 mol% or more. A particularly preferred embodiment is a polymer in which the sum of the hydroxycarboxylic acid residues and the lactone residues is 100% of the entire polymer, i.e., a polymer consisting only of hydroxycarboxylic acid residues and lactone residues.
[0059] The molar ratio of the hydroxycarboxylic acid residue to the lactone residue is preferably 7 / 3 to 3 / 7, more preferably 6 / 4 to 4 / 6, since the presence of either one in excess approaches homopolymer-like properties.
[0060] In addition, another monomer that can be copolymerized with the hydroxycarboxylic acid and lactone can be further copolymerized. Copolymerization of a monomer that functions as a linker is a preferred embodiment. Examples of monomers that function as linkers include hydroxycarboxylic acids other than the hydroxycarboxylic acids that constitute the main structural units, dialcohols, dicarboxylic acids, amino acids, diamines, diisocyanates, diepoxides, and the like. In this specification, the term "polyester copolymer" also includes copolymers that contain structural units that are linked in part by bonds other than ester bonds by including monomer units other than hydroxycarboxylic acids and lactones in the structural units.
[0061] The polyester copolymer is formed by copolymerizing a monomer that forms a hydroxycarboxylic acid residue (referred to as "monomer A") and a monomer that forms a lactone residue (referred to as "monomer B") in equimolar amounts, and the initial polymerization rate of each monomer is V A , V B When V is 1.1 or less, A / V BIt is preferable that the value satisfies ≦40.
[0062] Here, V A , V B can be determined by the following method. Equimolar amounts of monomer A and monomer B are mixed, a solvent and catalyst are added as necessary, and the polymerization reaction is started by adjusting the temperature and other conditions so that the R value obtained is the same as the R value, described below, of the polyester copolymer finally synthesized or to be synthesized within an error range of 10%. Sampling is taken periodically from the sample during polymerization, and the remaining amounts of monomer A and monomer B are measured. The remaining amounts are measured, for example, by chromatography or nuclear magnetic resonance (NMR) measurement. The amount of monomer used in the polymerization reaction can be determined by subtracting the remaining amounts from the charged amounts. When the amount of monomer used in the polymerization reaction is plotted against the sampling time, the initial slope of the curve is V A , V B It is.
[0063] When such monomer A and monomer B are reacted, there is a high probability that monomer A will bond to the end of the polymer during polymerization in the early stages of polymerization. On the other hand, in the later stages of polymerization when monomer A is consumed and the concentration of monomer A in the reaction solution decreases, there is a high probability that monomer B will bond to the end of the polymer during polymerization. As a result, a gradient polymer is obtained in which the proportion of monomer A residues is high at one end and gradually decreases toward the other end. Such a gradient polymer has low crystallinity and suppresses the increase in Young's modulus. To facilitate the formation of such a gradient structure, V A / V B is more preferably 1.3 or more, and even more preferably 1.5 or more. On the other hand, if the difference in the polymerization rate between monomer A and monomer B is too large, the resulting structure is similar to a block polymer in which only monomer A is polymerized and then monomer B is polymerized, and the crystallinity becomes high, which may lead to an increase in Young's modulus. A / V B is more preferably 30 or less, even more preferably 20 or less, and even more preferably 10 or less.
[0064] Such preferred combinations of monomer A and monomer B include dilactide and ε-caprolactone, glycolide and ε-caprolactone, dilactide and dioxepanone, dilactide and δ-valerolactone, and glycolide and δ-valerolactone.
[0065] The polyester copolymer contained in the connecting layer preferably satisfies the following conditions (A) and (B): The molar fraction in the polyester copolymer is a percentage relative to 100% of all monomer residues constituting the polyester copolymer.
[0066] Condition (A) The R value is 0.45 or greater and 0.99 or less.
[0067] R value = [AB] / (2[A][B]) x 100 [A]: Molar fraction (%) of hydroxycarboxylic acid residues in the polyester copolymer [B]: Molar fraction (%) of lactone residues in the polyester copolymer [AB]: mole fraction (%) of structures (AB and BA) in which a hydroxycarboxylic acid residue and a lactone residue are adjacent to each other in the polyester copolymer Condition (B) The crystallinity of at least one of the hydroxycarboxylic acid residue and the lactone residue is less than 14%.
[0068] The R value is used as an index of the randomness of the arrangement of monomer residues in a copolymer whose main structural units are two types of monomer residues, i.e., hydroxycarboxylic acid residues and lactone residues. For example, in a random copolymer in which the monomer arrangement is completely random, the R value is 1. In addition, in a block copolymer, the R value is 0 to 0.44.
[0069] The R value can be determined by quantifying the ratio of the combinations of two adjacent monomers (AA, BB, AB, BA) by nuclear magnetic resonance (NMR) measurement. Specifically, it is measured by the method described in Measurement Example 2 below. If the R value is less than 0.45, the crystallinity is high, and the molded product of the copolymer becomes hard and the Young's modulus increases. On the other hand, if the R value exceeds 0.99, the molded product of the copolymer becomes too soft and sticky, and the handling property decreases. From the same viewpoint, the R value of the polyester copolymer used in the present invention is preferably 0.50 or more and 0.80 or less.
[0070] It is also known that the crystallinity of a polymer has a large effect on the mechanical strength of the molded product. Generally, low crystallinity polymers show a low Young's modulus, so low crystallinity is desirable for flexibility. The crystallinity of a polymer can be determined from the heat of fusion by differential scanning calorimetry (DSC) measurement.
[0071] In the polyester copolymer, the crystallinity of at least one of the hydroxycarboxylic acid residues and the lactone residues is preferably less than 14%. If the crystallinity is less than 14%, an increase in Young's modulus is suppressed, and a polyester copolymer suitable for forming a cylindrical body can be obtained. The crystallinity of the hydroxycarboxylic acid residues and / or the lactone residues is more preferably 10% or less, and even more preferably 5% or less.
[0072] The crystallization rate of a monomer residue referred to here is the relative value of the heat of fusion per unit weight of a monomer residue in a polyester copolymer when the heat of fusion per unit weight of a homopolymer consisting of only a certain monomer residue is taken as 100%. Specifically, the crystallization rate of a hydroxycarboxylic acid residue is a ratio calculated by using the product of the heat of fusion per unit weight of a homopolymer consisting of only that hydroxycarboxylic acid and the weight fraction of that hydroxycarboxylic acid residue in the polyester copolymer as the denominator and the heat of fusion per unit weight of the polyester copolymer of that residue, which is determined from the melting peak derived from that hydroxycarboxylic acid residue detected when the heat of fusion of the polyester copolymer is measured. The crystallization rate of the hydroxycarboxylic acid residue and lactone residue in a polyester copolymer indicates the proportion of the hydroxycarboxylic acid residue and lactone residue forming a crystalline structure in the copolymer. Specifically, the crystallization rate is determined by the method described in Measurement Example 4 below.
[0073] Furthermore, since the present invention is used by being placed in the body, it is preferable that the polyester copolymer used is a bioabsorbable polyester copolymer with a proven track record of clinical safety. That is, it is preferable that the connecting layer contains a dilactide / ε-caprolactone copolymer, and that the dilactide / ε-caprolactone copolymer satisfies the following conditions (C) and (D). The molar fraction in the dilactide / ε-caprolactone copolymer is the percentage of the dilactide / ε-caprolactone copolymer relative to the total of 100% of dilactide residues and ε-caprolactone residues.
[0074] Condition (C) The R value is 0.45 or greater and 0.99 or less.
[0075] R value = [AB] / (2[A][B]) x 100 [A]: Molar fraction (%) of dilactide residues in dilactide / ε-caprolactone copolymer [B]: Molar fraction (%) of ε-caprolactone residues in the dilactide / ε-caprolactone copolymer [AB]: The mole fraction (%) of structures (AB and BA) in which dilactide residues and ε-caprolactone residues are adjacent to each other in the dilactide / ε-caprolactone copolymer. Condition (D) The crystallinity of at least one of the dilactide residues and the ε-caprolactone residues is less than 14%.
[0076] As an example of the polyester copolymer as described above, a macromer synthesis step of blending and polymerizing a monomer A forming a hydroxycarboxylic acid residue and a monomer B forming a lactone residue such that the sum of the hydroxycarboxylic acid residues and the lactone residues is 50 mol % or more of the total residues and the hydroxycarboxylic acid residues and the lactone residues are each 20 mol % or more of the total residues at the completion of the polymerization; a multi-polymerization step of linking the macromers obtained in the macromer synthesis step to each other or adding a hydroxycarboxylic acid and a lactone to the macromer solution obtained in the macromer synthesis step to multi-polymerize the macromers; The compound can be prepared by a synthetic method having the following structure:
[0077] In the macromer synthesis step, monomer A forming a hydroxycarboxylic acid residue and monomer B forming a lactone residue are mixed and polymerized so that, theoretically, at the completion of polymerization, the sum of hydroxycarboxylic acid residues and lactone residues is 50 mol % or more of all residues, and hydroxycarboxylic acid residues and lactone residues are each 20 mol % or more of all residues. This produces a polyester copolymer having hydroxycarboxylic acid residues and lactone residues as main structural units, but since this production method further includes a multi-formation step described later, in this specification, the polyester copolymer obtained by this step is referred to as a "macromer."
[0078] The randomness of the distribution of hydroxycarboxylic acid residues and lactone residues varies depending on the difference in the reactivity of the monomers during polymerization. That is, if one of the two types of monomers is bound to the same monomer and the other monomer with equal probability during polymerization, a random copolymer in which the monomer residues are distributed completely randomly is obtained. However, if there is a tendency for one monomer to be bound to the other monomer, a gradient copolymer in which the distribution of monomer residues is biased is obtained. The composition of the monomer residues in the resulting gradient copolymer changes continuously along the molecular chain from the polymerization initiation end to the polymerization termination end.
[0079] Here, since hydroxycarboxylic acids are generally monomers with a higher initial polymerization rate than lactones, when hydroxycarboxylic acids and lactones are copolymerized in the macromer synthesis step, the hydroxycarboxylic acids are likely to be bonded after the hydroxycarboxylic acids. Therefore, in the synthesized macromer, a gradient structure is formed in which the proportion of hydroxycarboxylic acid units gradually decreases from the polymerization initiation end to the polymerization termination end. In other words, the macromer obtained in this step has a gradient structure in which hydroxycarboxylic acid residues and lactone residues form a composition gradient in the skeleton due to the difference in the initial polymerization rates between hydroxycarboxylic acids and lactones. Such macromers may be referred to as "gradient macromers" in this specification.
[0080] In order to realize such a gradient structure in the macromer synthesis step, it is desirable to synthesize the macromer by a polymerization reaction that occurs in one direction from the initiation terminal. Preferred examples of such a synthesis reaction include ring-opening polymerization and living polymerization.
[0081] The macromer obtained in this step has an R value similar to that of the above condition (A), that is, the R value of the macromer represented by the following formula is preferably satisfied in order to facilitate the final production of a polyester copolymer that satisfies the R value of the above condition (A). R value = [AB] / (2[A][B]) x 100 [A]: Molar fraction (%) of hydroxycarboxylic acid residues in the macromer [B]: Molar fraction (%) of lactone residues in the macromer [AB]: Molar fraction (%) of structures (AB and BA) in which a hydroxycarboxylic acid residue and a lactone residue are adjacent to each other in the macromer The R value represented by the following formula is preferably 0.45 or more and 0.99 or less, and more preferably 0.50 or more and 0.80 or less.
[0082] Similarly, in order to facilitate the final production of a polyester copolymer having the crystallization rate of the hydroxycarboxylic acid residues or lactone residues specified in the above condition (B), the macromer obtained in this step preferably has a crystallization rate similar to that specified in the above condition (B), i.e., the crystallization rate of at least one of the hydroxycarboxylic acid residues or lactone residues is less than 14%, more preferably 10% or less, even more preferably 5% or less, and most preferably 1% or less.
[0083] The weight average molecular weight of the macromer synthesized in the macromer synthesis step is preferably 10,000 or more, more preferably 20,000 or more. In order to suppress crystallinity and maintain flexibility, the weight average molecular weight is preferably 150,000 or less, more preferably 100,000 or less.
[0084] In the multi-formation step, the macromers obtained in the macromer synthesis step are linked together, or a hydroxycarboxylic acid and a lactone are added to the macromer solution obtained in the macromer synthesis step to form a multi-formation. In this step, the macromers obtained in one macromer synthesis step may be linked together, or multiple macromers obtained in two or more macromer synthesis steps may be linked. Note that "multi-formation" means that, by either of these methods, a structure is formed in which multiple molecular chains having a gradient structure in which hydroxycarboxylic acid residues and lactone residues have a composition gradient in the skeleton are repeated.
[0085] The number of multi-formed macromer units may be 2 or more, but since a larger number of connections has the effect of improving tensile strength due to entanglement of molecular chains, it is preferably 3 or more, more preferably 4 or more, and even more preferably 6 or more. On the other hand, if the molecular weight of the polyester copolymer increases excessively as a result, there is a concern that the viscosity will increase and this will have an adverse effect on moldability, so the number of macromer units is preferably 80 or less, more preferably 40 or less, and even more preferably 20 or less.
[0086] The number of linked macromer units can be adjusted by the catalyst used in the multi-polymerization step and the reaction time. When linking macromers together to form a multi-polymer, the number of macromer units can be determined by dividing the weight average molecular weight of the final polyester copolymer by the weight average molecular weight of the macromer.
[0087] The polyester copolymer may be a linear polymer in which macromer units are linked in a straight line, or a branched polymer in which macromer units are linked in a branched manner.
[0088] A linear polyester copolymer can be synthesized, for example, by bonding one molecule of a gradient macromer to each end of a gradient macromer via the ends.
[0089] When the gradient macromer has a hydroxyl group and a carboxyl group at each end, the ends are condensed with a condensing agent to obtain a multi-polyester copolymer. Examples of the condensing agent include 4,4-dimethylaminopyridinium p-toluenesulfonate, 1-[3-(dimethylamino)propyl]-3-ethylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, N,N'-carbonyldiimidazole, 1,1'-carbonyldi(1,2,4-triazole), 4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium, and the like. ammonium chloride n hydrate, (4,6-dimethoxy-1,3,5-triazin-2-yl)-(2-octoxy-2-oxoethyl)dimethylammonium trifluoromethanesulfonate, 1H-benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, 1H-benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate, (7-azabenzotriazol-1-yloxy)tripyrrolidinophosphonium hexafluorophosphate, Lorotripyrrolidinophosphonium hexafluorophosphate, Bromotris(dimethylamino)phosphonium hexafluorophosphate, 3-(diethoxyphosphoryloxy)-1,2,3-benzotriazin-4(3H)-one, O-(benzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, O-(7-azabenzotriazol-1-yl)-N,N',N'-tetramethyluronium hexafluorophosphate, O-(N-succinimidyl)-N,N, N',N'-Tetramethyluronium tetrafluoroborate, O-(N-Succinimidyl)-N,N,N',N'-Tetramethyluronium hexafluorophosphate, O-(3,4-Dihydro-4-oxo-1,2,3-benzotriazin-3-yl)-N,N,N',N'-Tetramethyluronium tetrafluoroborate, S-(1-Oxido-2-pyridyl)-N,N,N',N'-Tetramethylthiuronium tetrafluoroborate, O-[2-Oxo-1(2H)-pyridyl]-N,N,N',N'-tetramethyluronium tetrafluoroborate, {{[(1-cyano-2-ethoxy-2-oxoethylidene)amino]oxy}-4-morpholinomethylene}dimethylammonium hexafluorophosphate, 2-chloro-1,3-dimethylimidazolinium hexafluorophosphate, 1-(chloro-1-pyrrolidinylmethylene)pyrrolidinium hexafluorophosphate, 2-fluoro-1,3-dimethylimidazolinium hexafluorophosphate, fluoro-N,N,N',N'-tetramethylformamidinium hexafluorophosphate, and the like can be used.
[0090] Furthermore, when the polymerization reaction has a living nature, i.e., when the polymerization reaction can be initiated continuously from the terminal of the polymer, multimerization can be achieved by repeatedly adding hydroxycarboxylic acid and lactone to the gradient macromer solution after the polymerization reaction is completed.
[0091] Alternatively, gradient macromers may be multi-linked via a linker as long as the mechanical properties of the polymer are not affected. In particular, by using a linker having multiple carboxyl groups and / or multiple hydroxyl groups, such as 2,2-bis(hydroxymethyl)propionic acid, a branched polyester copolymer can be synthesized in which the linker is the branch point.
[0092] The polyester copolymer obtained by the above-mentioned production method is a copolymer having a structure in which two or more macromer units having a composition gradient in the skeleton of hydroxycarboxylic acid residues and lactone residues are linked together. In this specification, such a structure may be referred to as "multi-gradient" for convenience, and a copolymer having a multi-gradient structure may be referred to as "multi-gradient copolymer". The multi-gradient copolymer preferably has a structure in which two or more macromer units having a gradient structure in which hydroxycarboxylic acid residues and the lactone residues form a composition gradient in the skeleton are linked together, and more preferably has a structure in which three or more macromer units are linked together.
[0093] As mentioned above, polyester copolymers in which the hydroxycarboxylic acid residue is a lactic acid residue and the lactone residue is a caprolactone residue or a valerolactone residue are particularly preferred for use in the tie layer. Such polyester copolymers are preferably produced by the following production method.
[0094] First, in the macromer synthesis process, dilactide and ε-caprolactone (or valerolactone; the same applies below) are polymerized in the presence of a catalyst. The dilactide and ε-caprolactone monomers are preferably purified to remove impurities before use. Dilactide can be purified, for example, by recrystallization from toluene dried with sodium. ε-caprolactone can be purified, for example, by vacuum distillation from CaH2 under a N2 atmosphere.
[0095] The reactivity of dilactide and ε-caprolactone is significantly different as described in the literature (DW Grijpma et al. Polymer Bulletin 25, 335, 341), and the initial polymerization rate of dilactide monomer is higher than that of ε-caprolactone. A The reaction rate (%) was 3.6% / h, and the V B is 0.88% / h, and V A / V B is 4.1. Therefore, the macromer obtained by copolymerizing dilactide and ε-caprolactone is a gradient macromer.
[0096] As a catalyst for the synthesis step of a macromer having a lactic acid residue and a caprolactone residue, a polyester polymerization catalyst such as a normal germanium-based, titanium-based, antimony-based, or tin-based catalyst can be used. Specific examples of such polyester polymerization catalysts include tin octylate, antimony trifluoride, zinc powder, dibutyltin oxide, and tin oxalate. The method of adding the catalyst to the reaction system is not particularly limited, but it is preferably added in a state where it is dispersed in the raw materials when the raw materials are charged, or in a state where it is dispersed at the start of the pressure reduction. The amount of the catalyst used is 0.01 to 3% by weight, more preferably 0.05 to 1.5% by weight, calculated as metal atoms, based on the total amount of the monomers used.
[0097] A macromer having lactic acid residues and caprolactone residues can be obtained by placing dilactide, caprolactone, and a catalyst in a reaction vessel equipped with a stirrer and reacting them at 150 to 250°C under a nitrogen stream. When water is used as a co-initiator, it is preferable to carry out a co-catalyst reaction at about 90°C prior to the polymerization reaction. The reaction time is 2 hours or more, preferably 4 hours or more, and in order to increase the degree of polymerization, a longer time, such as 8 hours or more, is preferable. However, if the reaction is carried out for too long, the polymer will become discolored, so the reaction time is preferably 3 to 12 hours.
[0098] Next, in the multi-polymerization step, the ends of the gradient macromers having lactic acid residues and caprolactone residues are linked to each other by a condensation reaction to form a multi-polymer. The reaction temperature for the condensation reaction is preferably 10 to 100°C, more preferably 20 to 50°C. The reaction time is preferably 1 day or more, more preferably 2 days or more. However, if the reaction is carried out for too long, the polymer will become discolored, so the reaction time is preferably 2 to 4 days.
[0099] <Cylindrical body> The cylindrical body constituting the cylindrical molded article for medical device of the present invention preferably contains the biodegradable polymer fiber described above. Examples of the structure of the cylindrical body include knitting, weaving, orientation, and nonwoven fabric. Among these, a nonwoven fabric structure is preferable. In a nonwoven fabric structure, the fibers are three-dimensionally and irregularly entangled with each other, resulting in a large number of voids, and the effect of improving permeability due to the increased fiber diameter is more pronounced.
[0100] As a method for manufacturing a cylindrical body, the above-mentioned polymer can be used to mold into a cylindrical shape using a melt molding method or a solvent molding method. The melt molding method is a method in which a polymer is heated and melted, and molded using a mold, an extrusion molding machine, a press machine, electrospinning, melt blowing, or the like. For example, the polymer can be molded into a cylindrical shape by heating it to 200°C in an extrusion molding machine set with a core inlet metal of φ0.5 to 4 mm and extruding it. The solvent molding method is a method in which a polymer is dissolved in a solvent, injected into a mold or a coagulation bath, and molded by separating the solvent and the solute, or an electrospinning method or a spray method. As an example of the solvent molding method, a rod of φ0.5 to 4 mm is immersed in a polymer solution dissolved at 20% in chloroform, and then pulled out, and after waiting for the solvent to evaporate, the rod is immersed again, and this is repeated about 5 to 10 times to mold into a cylindrical shape. In addition, a rod of φ0.5 to 4 mm can be molded into a cylindrical shape by depositing fibers in a cylindrical shape using an electrospinning method.
[0101] The cylindrical molded body thus obtained can be cut with a razor or the like to obtain a cylindrical body of a desired length.
[0102] The thickness of the cylindrical body is preferably 100 μm or more, more preferably 200 μm or more, from the viewpoint of improving the strength. Here, the thickness of the cylindrical body can be measured by enlarging and observing the cross section of the cylindrical body using a microscope. The thickness of the cylindrical body can be adjusted to a desired range by, for example, the spinning time by the electrospinning method.
[0103] <Method of manufacturing cylindrical molded body> For example, a material constituting a connecting layer may be applied to a plurality of cylindrical bodies produced as described above to connect two cylindrical bodies, thereby producing the cylindrical molded body for medical devices of the present invention. Examples of a method for applying the connecting layer include electrospinning.
[0104] One example of a manufacturing method is as follows: (1) the bioabsorbable polymer that constitutes the tubular body is formed into fibers by electrospinning, and these are accumulated on a collector; (2) the tubular body together with the collector is retrieved, and a slit is made at any desired location in the direction of the rotation of the collector with a razor or the like; and (3) the fiber aggregate with the slit obtained in step (2) is set again in the electrospinning device, and the bioabsorbable polymer that constitutes the connecting layer is formed into fibers by electrospinning, and these are accumulated on the tubular body.
[0105] The obtained molded article can be used as a nerve regeneration guide tube to protect regenerating nerves by attaching it to both ends of a severed nerve. EXAMPLES
[0106] The present invention will be described below using specific examples. However, the present invention should not be interpreted as being limited to these examples. It should be understood that the present invention includes all technical ideas and specific embodiments thereof that a person skilled in the art who comes into contact with the concept of the present invention would conceive and consider to be feasible.
[0107] [Measurement Example 1: Measurement of weight average molecular weight by gel permeation chromatography (GPC)] Device name: Prominence (manufactured by Shimadzu Corporation) Mobile phase: Chloroform (for HPLC) (manufactured by Wako Pure Chemical Industries, Ltd.) Flow rate: 1mL / min Column: TSKgel GMHHR-M (φ7.8mm x 300mm; manufactured by Tosoh Corporation) Detector: UV (254 nm), RI Column and detector temperature: 35℃ Standard material: polystyrene The purified polymer was dissolved in chloroform and passed through a 0.45 μm syringe filter (DISMIC-13HP; manufactured by ADVANTEC) to remove impurities, and then the polymer was measured by GPC to calculate the weight average molecular weight.
[0108] [Measurement Example 2: Measurement of the molar fraction and R value of each residue by nuclear magnetic resonance (NMR)] The purified polymer was dissolved in deuterated chloroform. 1 The ratios of lactic acid monomer residues and caprolactone monomer residues in the polymer were calculated by H-NMR. 1 Using the H homospin decoupling method, the methylene group of lactic acid (around 5.10 ppm), the α-methylene group of caprolactone (around 2.35 ppm), and the ε-methylene group (around 4.10 ppm) were separated by signal to determine whether the adjacent monomer residues were derived from lactic acid or caprolactone, and the peak areas of each were quantified. [A], [B], and [AB] were calculated from the peak area ratios, and the R value was calculated. Device name: JNM-EX270 (manufactured by JEOL Ltd.) 1 H homospin decoupling irradiation position: 1.66 ppm Solvent: deuterated chloroform Measurement temperature: room temperature R value = [AB] / (2[A][B]) x 100 [A]: Molar fraction (%) of lactic acid monomer residues in the polymer [B]: Molar fraction (%) of caprolactone monomer residues in the polymer [AB]: The mole fraction (%) of structures in which a lactic acid monomer residue and a caprolactone monomer residue are adjacent to each other (AB and BA) in the polymer.
[0109] [Measurement example 3: Tensile test] The polymer was dried under reduced pressure and dissolved in chloroform to a concentration of 5% by weight. The solution was transferred onto a Teflon petri dish and dried at room temperature under normal pressure for one day and night. The solution was then dried under reduced pressure to obtain a film.
[0110] The dried film (approximately 0.1 mm thick) was cut into a 50 mm x 5 mm piece, and a tensile test was performed using a tabletop tensile tester (Shimazu EZ-LX) according to JIS K6251 (2010) under the following conditions to calculate the breaking elongation and tensile strength. Furthermore, in a graph plotting stress against displacement, the slope of a linear equation that can be approximated from the data of five points from the start of stress generation was calculated as Young's modulus. Equipment name: Tabletop tensile testing machine (SHIMAZU EZ-LX) Initial length: 10mm Tensile speed: 500mm / min Load cell: 1kN Number of tests: 5.
[0111] [Measurement Example 4: Measurement of crystallization rate of lactic acid residues by differential scanning calorimetry (DSC)] The purified polymer was dried under reduced pressure, dissolved in chloroform to a concentration of 5% by weight, and the solution was transferred onto a Teflon petri dish and dried at room temperature under normal pressure for one day and night. This was then dried under reduced pressure to obtain a film.
[0112] The obtained film was collected on an alumina PAN and measured by a differential scanning calorimeter under the following conditions by the DSC method, and the heat of fusion was calculated from the measurement results in the range of temperature conditions (D) to (E). The crystallization rate was calculated from the following formula.
[0113] Crystallization rate=(Heat of fusion of lactic acid residues per unit weight of polyester copolymer) / {(Heat of fusion of homopolymer consisting of only lactic acid residues per unit weight)×(Weight fraction of lactic acid residues in polyester copolymer)}×100 Device name: EXSTAR 6000 (Seiko Instruments Inc.) Temperature conditions: (A) 25℃ → (B) 250℃ (10℃ / min) → (C) 250℃ (5min) → (D) -70℃ (10℃ / min) → (E) 250℃ (10℃ / min) → (F) 250℃ (5min) → (G) 25℃ (100℃ / min) Standard material: alumina.
[0114] [Measurement Example 5: Measurement of work conservation rate and permanent deformation] The purified polymer was dried under reduced pressure, dissolved in chloroform to a concentration of 5% by weight, and the solution was transferred onto a Teflon petri dish and dried at room temperature under normal pressure for one day and night. This was then dried under reduced pressure to obtain a film.
[0115] The film (approximately 0.1 mm thick) was cut into a rectangular shape (50 mm x 5 mm) and set in a tabletop tensile tester (Shimazu EZ-LX). Under the conditions below, the film was stretched from an initial length (L0) of 10 mm to a tensile length (L) of 10 mm, i.e., until the tensile strain reached 100%, and then restored to the initial length (L0). This operation was repeated 10 times, and the changes in tensile stress and displacement were recorded. Equipment name: Tabletop tensile testing machine (SHIMAZU EZ-LX) Holding time: 1s Tensile speed: 500mm / min Recovery speed: 500mm / min Load cell: 1kN When the stress for displacement (X1, X2, ) is (N1, N2, ), the amount of work (W) required to produce 100% tensile strain is equal to the area under the displacement-stress curve and can be calculated using the following formula. W=ΣN n (X n -X n-1 ) where X0=0. The first W is W1, the 10th W is W 10 Then, the work conservation rate (%) = W 10 / W1×100.
[0116] As described above, the stretching and restoration operations are repeated 10 times to measure the work retention rate, and then the film is stretched again at the same tensile speed to record the changes in tensile stress and displacement. The displacement at which stress begins to occur is defined as L1. The permanent set can be calculated using the following formula. Permanent set (%) = L1 / L0 x 100.
[0117] [Measurement Example 6: Kinking Suppression Test for Cylindrical Molded Body] A wire with a total length of 6 cm was prepared. Starting from the center of the wire, it was bent at a 180° angle (straight), a 120° angle, a 90° angle, and a 60° angle.
[0118] The cylindrical molded bodies for medical devices were cut to a length of 40 mm, and the wires prepared above were passed through the insides and bent to the shape of each wire. After that, when the upper inside parts of both ends of the molded bodies were pressed against the wires, it was visually observed whether kinks occurred in the molded bodies at the corners of each wire. When kinks were observed, it was recorded as "present", and when kinks were not observed, it was recorded as "absent".
[0119] [Measurement Example 7: Pressure resistance test of cylindrical molded body] The total length of the cylindrical molded body for medical devices was adjusted to 20 mm, and a compression test was carried out under the following conditions using a benchtop tensile tester (EZ-LX manufactured by SHIMAZU). The pressure at which the height reached 50% of the initial height was recorded. Equipment name: Tabletop tensile testing machine (SHIMAZU EZ-LX) Compression distance: 6mm Holding time: 1s Compression speed: 10mm / min Load cell: 1kN.
[0120] [Measurement Example 8: Tensile test of cylindrical body and cylindrical molded body] The Young's modulus of the cylindrical body was measured by cutting the cylindrical body before cutting to a length of 20 mm, and carrying out a tensile test under the following conditions using a tabletop tensile tester (Shimazu EZ-LX) to determine the Young's modulus, elongation, and breaking strength. The Young's modulus of the cylindrical molded body was measured by cutting the cylindrical molded body to a length of 20 mm and carrying out the same test. Note that, since only the connecting layer expands and contracts in the tensile test of the cylindrical molded body, the Young's modulus, elongation, and breaking strength obtained in the tensile test of the cylindrical molded body were treated as the Young's modulus, elongation, and breaking strength of the connecting layer. Equipment name: Tabletop tensile testing machine (SHIMAZU EZ-LX) Initial length (L0): 10mm Tensile speed: 500mm / min. Load cell: 1kN.
[0121] <Example 1> (Cylindrical body production) Poly-L-lactic acid (PLLA) (BMG Co., Ltd., Mw=220,000, Mw / Mn=1.51) was dissolved in chloroform to a concentration of 20% by weight. The PLLA solution was collected in a 5 mL syringe (Terumo Co., Ltd.), and an 18G needle (MECC Co., Ltd.) dedicated to MECC's spinning device NANON-3 was attached to the syringe. The syringe containing the PLLA solution and a φ4 mm metal mandrel were set in the spinning device NANON-3, and the PLLA solution was spun onto the mandrel by electrospinning to obtain a PLLA cylindrical body. The spinning conditions were as follows: spinning distance: 15 cm, spinning voltage: 25 kV, spinning speed: 3 mL / hour, rotation speed: 50 to 100 rpm, spinning amplitude: 15 cm, and spinning time: 60 minutes. After spinning, the obtained cylindrical body (before cutting) was vacuum dried overnight at room temperature together with the mandrel without being removed. The thickness of the PLLA layer forming the cylindrical body was measured with a microscope (Hirox KH-1300) and found to be 487 μm. Thereafter, without removing the cylindrical body (before cutting) from the mandrel, a microtome blade (Feather Safety Razor Co., Ltd., S35TYPE, standard product) was used to cut the cylindrical body (before cutting) by making incisions every 5 mm in the circumferential direction (entire circumference) to produce a cylindrical body (after cutting).
[0122] (Synthesis of polymer for tie layer) The polymer for the connecting layer was synthesized as follows. 50.0 g of L-lactide (PURASORB L; manufactured by PURAC) and 38.5 mL of ε-caprolactone (manufactured by Wako Pure Chemical Industries, Ltd.) were collected in a separable flask as monomers. The flask was placed under an argon atmosphere, and 0.81 g of tin(II) octylate (manufactured by Wako Pure Chemical Industries, Ltd.) dissolved in 14.5 mL of toluene (ultra-dehydrated) (manufactured by Wako Pure Chemical Industries, Ltd.) as a catalyst and ion-exchanged water as a co-initiator were added in an amount such that the monomer / co-initiator ratio was 142.9. After the co-catalyst reaction was carried out at 90°C for 1 hour, the copolymerization reaction was carried out at 150°C for 6 hours to obtain a crude copolymer.
[0123] The resulting crude copolymer was dissolved in 100 mL of chloroform and added dropwise to 1400 mL of methanol under stirring to obtain a precipitate. This procedure was repeated three times, and the precipitate was then dried under reduced pressure at 70° C. to obtain a macromer.
[0124] 7.5 g of the macromer, 0.28 g of 4,4-dimethylaminopyridinium p-toluenesulfonate (synthetic product) as a catalyst, and 0.10 g of 4,4-dimethylaminopyridine (manufactured by Wako Pure Chemical Industries, Ltd.) were collected. These were placed under an argon atmosphere and dissolved in dichloromethane (dehydrated) (manufactured by Wako Pure Chemical Industries, Ltd.) to a concentration of 30%. 0.47 g of amylene (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 5 mL of dichloromethane as a condensation agent was added thereto, and condensation polymerization was carried out at room temperature for 2 days.
[0125] 30 mL of chloroform was added to the resulting reaction mixture, and the mixture was dropped into 500 mL of hexane containing acetic acid at 15 mM while stirring to obtain a precipitate. The precipitate was dissolved in 50 mL of chloroform, and the mixture was dropped into 500 mL of methanol while stirring to obtain a precipitate. This operation was repeated twice to obtain a purified polyester copolymer as a precipitate.
[0126] The purified polyester copolymer thus obtained was measured by the methods described in Measurement Examples 1 to 5, and the results were as follows: weight average molecular weight was 240,000, copolymerization ratio was lactic acid:caprolactone=53.0:47.0 (weight ratio), R value was 0.60, crystallization rate was 0%, Young's modulus was 2.98 MPa, tensile strength was 33.7 MPa, break elongation was 1032%, work retention rate was 57.5%, and permanent set was 20%.
[0127] (Preparation of a cylindrical molded body for medical devices (a molded body in which multiple cylindrical bodies are connected with a connecting layer)) The mandrel having the cylindrical body (after cutting) cut in the above "Preparation of cylindrical body" was set again in the spinning apparatus NANON-3. The polymer for the connection layer synthesized as described above was dissolved in chloroform so that the concentration was 30% by weight. The polymer solution for the connection layer was collected in a 5 mL syringe (Terumo Corporation), and an 18G needle (MECC Corporation) dedicated to the spinning apparatus NANON-3 of MECC Corporation was attached to the syringe. The syringe containing the polymer solution for the connection layer was set in the spinning apparatus NANON-3, and the polymer solution for the connection layer was spun onto the mandrel having the cylindrical body (after cutting) by electrospinning, thereby creating a connection layer on the outside of the cylindrical body (after cutting). The spinning conditions were as follows: spinning distance: 15 cm, spinning voltage: 30 kV, spinning speed: 3 mL / hour, rotation speed: 50 to 100 rpm, spinning amplitude: 15 cm, and spinning time: 60 minutes. After spinning, the cylindrical molded body was vacuum-dried at room temperature overnight together with the mandrel without being removed. The mandrel was then removed to obtain a cylindrical molded body for medical devices in which multiple cylindrical bodies were connected by a connecting layer. The thickness of the cylindrical molded body including the connecting layer was measured with a microscope (Hirox KH-1300), and the thickness of the connecting layer was calculated to be 309 μm by subtracting the thickness of the PLLA layer forming the cylindrical body.
[0128] The cylindrical molded body for medical device of Example 1 was composed of multiple cylindrical bodies, each 5 mm in length, arranged at intervals of 0.2 mm, and the multiple cylindrical bodies were connected by a connecting layer, which was arranged in contact with the outside of the cylindrical bodies.
[0129] To measure the Young's modulus of the cylindrical body, a cylindrical body cut to 20 mm was prepared in the same manner as in "Preparation of cylindrical body" above, except that the cutting interval was 20 mm. As described in Measurement Example 8, the prepared 20 mm cylindrical body was set in a testing machine so that the initial length was 10 mm, and a tensile test was performed. The Young's modulus of the cylindrical body was 34.8 MPa.
[0130] The obtained cylindrical molded body for medical device was subjected to a kink generation suppression test described in Measurement Example 6 and a pressure resistance test described in Measurement Example 7, and the results are shown in Table 1. Fig. 5 shows a photograph of the cylindrical molded body bent at a 60° angle in Measurement Example 6. As shown in Fig. 5, no kinking occurs in the cylindrical molded body of Example 1 even when bent at a 60° angle. In the photograph, the thin object inserted into the cylindrical molded body is a wire.
[0131] As described above, the Young's modulus of the cylindrical body was 6.3 MPa or more, and the Young's modulus of the connecting layer was less than 6.3 MPa.
[0132] <Comparative Example 1> A cylindrical body (before cutting) was produced in the same manner as in Example 1, and then a cylindrical molded body for a medical instrument was produced in the same manner as in Example 1, except that cutting with a microtome blade was not performed.
[0133] The obtained cylindrical molding was subjected to the kink generation suppression test described in Measurement Example 6 and the pressure resistance test described in Measurement Example 7, and the results are shown in Table 1. Since a kink occurred at an angle of 120°, it is clear that there is no effect of suppressing the kink generation.
[0134] Comparing Example 1 and Comparative Example 1, the 50% compression pressure is almost the same, so there is almost no difference in pressure resistance between Example 1 and Comparative Example 1. Despite this, no kinking occurs up to an angle of 60° in Example 1, which shows that kinking occurrence can be suppressed in Example 1.
[0135] <Example 2> (Cylindrical body production) A cylindrical body (before cutting) was produced in the same manner as in Example 1, except that a solution of glycolic acid / L-lactic acid copolymer (PGLA) (manufactured by BMG Co., Ltd., Mw=260,000, Mw / Mn=1.64, GA:LA=10.1:89.9) dissolved in chloroform to a concentration of 10% by weight was used instead of the PLLA solution as the polymer solution for producing the cylindrical body.
[0136] The thickness of the PGLA layer forming the cylindrical body was measured with a high-speed, high-precision dimension measuring device (Keyence Corporation, LS-9030) and found to be 336 μm. After that, without removing the cylindrical body (before cutting) from the mandrel, a microtome blade (Feather Safety Razor Corporation, S35 TYPE, standard product) was used to make cuts every 2.5 mm in the circumferential direction (entire circumference) of the cylindrical body (before cutting) to produce the cylindrical body (after cutting).
[0137] (Preparation of a cylindrical molded body for medical devices (a molded body in which multiple cylindrical bodies are connected with a connecting layer)) The mandrel having the tubular body (after cutting) cut in the above "Preparation of tubular body" was set again in the spinning device NANON-3. Using the polymer for the connecting layer described in Example 1, a tubular molded body for medical devices in which multiple tubular bodies were connected by the connecting layer was obtained in the same manner as in Example 1.
[0138] The thickness of the cylindrical molded body including the connecting layer was measured using a high-speed, high-precision dimension measuring device (LS-9030, manufactured by Keyence Corporation), and by subtracting the thickness of the PGLA layer forming the cylindrical body, the thickness of the connecting layer was calculated to be 362 μm.
[0139] Moreover, the Young's modulus of the cylindrical body was measured in the same manner as in Example 1 and was found to be 74.4 MPa.
[0140] The cylindrical molded body for medical device of Example 2 was composed of multiple cylindrical bodies, each 2.5 mm in length, arranged at intervals of 0.2 mm, and the multiple cylindrical bodies were connected by a connecting layer, which was arranged in contact with the outside of the cylindrical bodies.
[0141] The obtained cylindrically molded article for medical device was subjected to the kink generation suppression test described in Measurement Example 6 and the pressure resistance test described in Measurement Example 7, and the results are shown in Table 1. Note that, as shown in the photograph of FIG. 6, the cylindrically molded article of Example 2 did not generate kinks even when wound once, which is even stricter than the conditions of Measurement Example 6.
[0142] Furthermore, as a result of carrying out the tensile test described in Measurement Example 8, the Young's modulus was 1.5 MPa, the elongation was 1900%, and the breaking strength was 4.4 MPa.
[0143] <Example 3> (Cylindrical body production) A cylindrical body (before cutting) was produced in the same manner as in Example 1, except that a solution of glycolic acid / L-lactic acid copolymer (PGLA) (manufactured by BMG Co., Ltd., Mw=250,000, Mw / Mn=1.63, GA:LA=20.5:79.5) dissolved in chloroform to a concentration of 10% by weight was used instead of the PLLA solution as the polymer solution for producing the cylindrical body.
[0144] The thickness of the PGLA layer was measured with a high-speed, high-precision dimension measuring device (Keyence Corporation, LS-9030) and found to be 328 μm. After that, without removing the cylindrical body (before cutting) from the mandrel, a microtome blade (Feather Safety Razor Corporation, S35 TYPE, standard product) was used to make cuts every 2.5 mm in the circumferential direction (entire circumference) of the cylindrical body (before cutting) to produce the cylindrical body (after cutting).
[0145] (Preparation of a cylindrical molded body for medical devices (a molded body in which multiple cylindrical bodies are connected with a connecting layer)) The mandrel having the tubular body (after cutting) cut in the above "Preparation of tubular body" was set again in the spinning device NANON-3. Using the polymer for the connecting layer described in Example 1, a tubular molded body for medical devices in which multiple tubular bodies were connected by the connecting layer was obtained in the same manner as in Example 1.
[0146] The thickness of the cylindrical molded article including the connecting layer was measured with a high-speed, high-precision dimension measuring device (Keyence Corporation, LS-9030), and by subtracting the thickness of the PGLA layer, the thickness of the connecting layer was calculated to be 384 μm.
[0147] Moreover, when the Young's modulus of the cylindrical body was measured in the same manner as in Example 1, it was 79.2 MPa.
[0148] The cylindrical molded body for medical device of Example 3 was composed of multiple cylindrical bodies, each 2.5 mm in length, arranged at intervals of 0.2 mm, and the multiple cylindrical bodies were connected by a connecting layer, which was arranged in contact with the outside of the cylindrical bodies.
[0149] The obtained cylindrical molded article for a medical device was subjected to the kink generation inhibition test described in Measurement Example 6 and the pressure resistance test described in Measurement Example 7. The results are shown in Table 1.
[0150] Furthermore, as a result of carrying out the tensile test described in Measurement Example 8, the Young's modulus was 0.7 MPa, the elongation was 1200%, and the breaking strength was 4.3 MPa.
[0151] [Table 1] [Industrial Applicability]
[0152] The tubular molded body for medical devices of the present invention can be flexibly deformed in response to curvature or bending due to the flexible layer connecting multiple tubular bodies, and the occurrence of kinking can be suppressed, and therefore the tubular molded body for medical devices can be suitably used as a nerve regeneration induction tube, etc. [Explanation of symbols]
[0153] 10. Nerve regeneration induction tube 11 Scaffolding Materials 200 neurons 201 Axon 210 Schwann cells 211 Schwann cells A: One adjacent cylindrical body B: The other adjacent cylindrical body C connection layer
Claims
1. A nerve regeneration inducing tube having a plurality of cylindrical bodies and a connecting layer connecting the cylindrical bodies, The length of the cylindrical body in the direction along the longitudinal axis of the nerve regeneration-inducing tube is 1.0 mm to 10 mm; the tie layer comprises a polyester copolymer having hydroxycarboxylic acid residues and lactone residues as main building blocks, A nerve regeneration-inducing tube, wherein the polyester copolymer satisfies the following conditions (A) and (B): Condition (A) The R value is 0.45 or more and 0.99 or less; R value = [A B] / (2 [A] [B]) x 100 [A]: Molar fraction (%) of hydroxycarboxylic acid residues in the polyester copolymer [B]: mole fraction (%) of lactone residues in the polyester copolymer [AB]: mole fraction (%) of structures (AB and BA) in which a hydroxycarboxylic acid residue and a lactone residue are adjacent to each other in the polyester copolymer Condition (B) The crystallization rate of at least one of the hydroxycarboxylic acid residue and the lactone residue is less than 14%.
2. The nerve regeneration inducing tube according to claim 1 , wherein the distance between adjacent cylindrical bodies is 1 mm or less.
3. The nerve regeneration induction tube according to claim 1 or 2, wherein the tubular body and the connecting layer are in contact with each other, and the connecting layer is disposed on the outside of the tubular body.
4. The nerve regeneration induction tube according to any one of claims 1 to 3, wherein the cylindrical body and the connecting layer are in contact with each other, and the connecting layer is disposed inside the cylindrical body.
5. The nerve regeneration induction tube according to any one of claims 1 to 3, wherein the tubular body and the connecting layer are in contact with each other, and the connecting layer is disposed on the inside of one of the adjacent tubular bodies (tubular body A) and on the outside of the other tubular body (tubular body B).
6. The nerve regeneration induction tube according to any one of claims 1 to 5, wherein the Young's modulus of the cylindrical body is 6.3 MPa or more, and the Young's modulus of the connecting layer is less than 6.3 MPa.
7. the tie layer comprises a dilactide / ε-caprolactone copolymer; The nerve regeneration-inducing tube according to any one of claims 1 to 6, wherein the dilactide / ε-caprolactone copolymer satisfies the following conditions (C) and (D): Condition (C) The R value is 0.45 or more and 0.99 or less; R value = [A B] / (2 [A] [B]) x 100 [A]: Molar fraction (%) of dilactide residues in the dilactide / ε-caprolactone copolymer [B]: Molar fraction (%) of ε-caprolactone residues in the dilactide / ε-caprolactone copolymer [AB]: mole fraction (%) of structures (AB and BA) in which a dilactide residue and an ε-caprolactone residue are adjacent to each other in a dilactide / ε-caprolactone copolymer Condition (D) The crystallinity of at least one of the dilactide residues and the ε-caprolactone residues is less than 14%.
8. The nerve regeneration-inducing tube according to any one of claims 1 to 7, wherein the cylindrical body comprises a bioabsorbable polyester.
Citation Information
Patent Citations
Construction of force feed device
JP1988097887A
Nerve regeneration tube and method for manufacturing the same
JP2011206203A
Tubular body
JP2014155622A
Compression-resistant and kink-resistant implants
JP2015527895A
Polymeric tubes with controlled orientation
US20190118456A1